A decision support model in mass customization. (December 2017) - Xu, Yang; Landon, Yann; Segonds, Stéphane; Zhang, Yicha
Highlights: Decision support model in mass customization. Analysis of customer preference, product features and cost. Optimization using genetic algorithm. Abstract: Mass customization (MC) is one of the leading strategies used in production industries in today's market filled with competition. MC is an oxymoron of controlling production costs and satisfying customers' individual requirements. It is well known that economy of scale and economy of scope is a pair of conflicts, and how to get the balance between them is the key issue to promote enterprises' competition. By analyzing and processing information of customer preference, product features and cost, this paper proposes a decision support model in mass customization to obtain the optimized production solution. Genetic algorithm is used for optimization, and the results of an illustrative example show that the model is efficient in production industries.